BIOMARKERS FOR EARLY DETECTION OF DIABETIC NEPHROPATHY - P. Goycheva (Trakia Journal of Sciences, 2025)
Diabetic nephropathy (DN) is the most common complication of type 2 diabetes mellitus and is the leading cause of end-stage renal disease worldwide. Early detection of diabetic nephropathy (DN) is critical because timely intervention can help slow the loss of kidney function and mitigate negative outcomes. It is crucial to diagnose patients at an early stage of DN, which is reversible and with the possibility of better control of the progression of the complication. As an early marker of DN, microalbuminuria is used in routine practice for screening and onset of the complication. On the other hand, kidney damage can occur even without microalbuminuria. There are several significant biomarkers of kidney damage in diabetes that allow detection of diabetic nephropathy at an early stage. This is crucial for timely treatment that can delay the development of DN and its progression. Therefore, this review focuses on laboratory biomarkers that are early, specific and that could potentially enable early diagnosis, treatment and delay of progression of diabetic nephropathy.